An alternative method to isolate protease and phospholipase A2 toxins from snake venoms based on partitioning of aqueous two-phase systems - Gomez, Gabriela Noemi (2012)
Snake venoms are rich sources of active proteins that have been employed in the diagnosis and treatment of health disorders and antivenom therapy. Developing countries demand fast economical downstream processes for the purification of this biomolecule type without requiring sophisticated equipment. We developed an alternative, simple and easy to scale-up method, able to purify simultaneously protease and phospholipase A2 toxins from Bothrops alternatus venom. It comprises a multiple-step partition procedure with polyethylene-glycol/phosphate aqueous two-phase systems followed by a gel filtration chromatographic step. Two single bands in SDS-polyacrylamide gel electrophoresis and increased proteolytic and phospholipase A2 specific activities evidence the homogeneity of the isolated proteins.